2009
DOI: 10.1080/14999010903199258
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evidence of Adaptive Decision Making Techniques Used by Parole Board Members

Abstract: Given wide-ranging interest in the predictors of recidivism, it is surprising that relatively little research has focused on a major factor influencing offenders' ability to re-offendconditional release decisions. Using a correlational design and hypothetical offender vignettes, this study examined conditional release decisions in a sample of 31 parole board members from Canada and New Zealand. Results revealed marked inter-individual differences, not related to demographic characteristics, in the parole decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
0
17
0
2
Order By: Relevance
“…Parole release decisions are typically made under considerable time pressure and board members are often provided with large volumes of file information for each offender (Gobeil & Serin, 2009). In this context board members may simplify their decision-making process and focus on key variables considered to be associated with performance on parole and recidivism (Gobeil & Serin, 2009).…”
Section: Factors Considered In Parole Decisionmakingmentioning
confidence: 99%
“…Parole release decisions are typically made under considerable time pressure and board members are often provided with large volumes of file information for each offender (Gobeil & Serin, 2009). In this context board members may simplify their decision-making process and focus on key variables considered to be associated with performance on parole and recidivism (Gobeil & Serin, 2009).…”
Section: Factors Considered In Parole Decisionmakingmentioning
confidence: 99%
“…Atliekant tyrimą paaiškėjo, kad komisijos nariai dažniau pritardavo paleisti lygtinai nuteistas moteris, taip pat seksualinio pobūdžio nusikaltimus padariusius nuteistuosius. Tuo tarpu komisijų nariai dažniau nepritardavo smurtautojų artimoje aplinkoje lygtiniam paleidimui (Gobeil & Serin, 2009). Gauti duomenys parodė, kad dauguma tyrimo dalyvių, priimdami sprendimą, vadovavosi informacija apie kalinių nusikalstamą riziką bei paleidimo planą.…”
Section: 2 2 Subjektyvūs Sprendimo Dėl Asmens Lygtinio Paleidimunclassified
“…Bū-tinumas suderinti šiuos daugialypius interesus rodo, kad sprendimo dėl lygtinio paleidimo priėmimas nėra paprastas procesas (Gobeil & Serin, 2009). …”
Section: 2 2 Subjektyvūs Sprendimo Dėl Asmens Lygtinio Paleidimunclassified
“…Among forensic patients, there have been few studies examining factors associated with decision to approve leave (McDermott, Scott, Busse, Andrade, Zozaya, & Quanbeck, 2008) and factors underlying these decisions (Gobeil & Serin, 2009). McDermott and Thompson (2006) argue that, compared to the use of structured assessment by clinicians, "the need for data-driven decisions in forensic systems tasked with making release decisions is even more critical" (p. 110).…”
mentioning
confidence: 99%
“…Callahan and Silver (1998) found variability in leave decisions were influenced by an interaction of system structures and individual characteristics of patients. Gobeil and Serin (2009) suggested that parole board members are not following guidelines as intended and vary in the type of information taken into account when forming these important decisions.…”
mentioning
confidence: 99%